Effects of stress concentration on the mechanical properties of X70 in high-pressure hydrogen-containing gas mixtures. (23rd October 2020) - Shang, Juan; Zheng, Jinyang; Hua, Zhengli; Li, Yanhua; Gu, Chaohua; Cui, Tiancheng; Meng, Bo
Abstract: This study aims to investigate the mechanical properties of X70 pipeline steel under the synergistic influence of hydrogen and stress concentration. Slow strain rate tensile tests and low-cycle fatigue tests were performed on the specimens with different stress concentration factors ( Kt ) in 10 MPa nitrogen/hydrogen mixtures. Results show that the degradation degree of the ductility and fatigue life of X70 steel induced by hydrogen increases with the increase of Kt, and as the hydrogen partial pressure in mixtures increases, the influence of Kt on hydrogen-induced degradation increases as well. In addition, finite element analysis was performed via a modified hydrogen diffusion/plasticity coupled model to study the effect of Kt on hydrogen distribution in the specimens, which can influence the mechanical properties of X70. The maximum hydrogen concentration consistently appears at the notch tip of the specimen and increases with the increase of Kt, which is proposed to be one of the reasons for the severe hydrogen embrittlement of the specimens with large Kt . As the axial tensile force on the specimen increases, the maximum hydrogen concentration at the notch tip begins to be dominated by hydrogen in the normal interstitial lattice sites and, subsequently, in the trapping sites. Highlights: Tensile tests and fatigue tests were conducted on the notched specimens. Finite element analysis was used to study the hydrogen distribution in the specimens. Hydrogen concentration at the notch tip of specimens increases as the stress rises.